PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP NILAI KERJASAMA DAN HASIL BELAJAR KOGNITIF KIMIA SISWA KELAS X SMAN 1 BAMBANGLIPURO BANTUL - Rahmawati, Gita; Suprihatiningrum, Jamil (Kaunia: Integration and Interconnection Islam and Science Journal, 2014)
Cooperation value and students’ cognitive learning outcomes were examined as the effect of the implementation of cooperative learning – make a match. The Nonequivalent Control Pre-test dan Post-test Group Design as this quasi-experimental research was involved 1st grade students of SMAN 1 Bambanglipuro at academic year 2013/2014. Students at X4 as an experimental sampel and X3 as a control sampel were choosen by cluster random sampling technique. The data was collected using pre-test and post-test for hydrocarbon subject matter, cooperation scale, and observation scale, was then analyzed by t-test. The result shows there was no significant effect of cooperative learning – make a match toward to students’ cooperation value and cognitive learning outcomes, were proven by sig. (2-tailed) of t-test > 0.05 at 0.282 and sig. (2-tailed) of MannWhitney test > 0.05 at 0.953 respectively.